A retrospective analysis of the market price response to distributed photovoltaic generation in California. (October 2018) - Craig, Michael T.; Jaramillo, Paulina; Hodge, Bri-Mathias; Williams, Nathaniel J.; Severnini, Edson
Abstract: Due to rapid growth of distributed solar photovoltaic (PV) capacity in the U.S., numerous "value of solar" studies have attempted to quantify avoided costs associated with distributed PV. One such avoided cost that has received little attention is the market price response, or how distributed PV generation reduces utilities' procurement costs and, consequently, consumers' costs through reduced wholesale electricity prices in the short-term. We quantify the reduction in day-ahead wholesale electricity prices to distributed PV generation in California (CA) from 2013 through 2015. Using a database of all distributed PV systems in the three CA investor owned utilities, we estimate historic hourly distributed PV generation using three methods that we validate with metered generation from 205 PV systems. Via multiple linear regression, we then estimate electricity price reductions due to distributed PV generation. Across the three methods used to estimate PV generation, distributed PV generation reduced hourly median (mean) wholesale electricity prices by up to $2.7–3.1/MWh ($2.9–3.2/MWh) ($2015 ), or by 7–8% (8–9%). Lower wholesale prices reduced utilities' energy procurement costs in the day-ahead market by up to $650–730 million ($2015 ) from 2013 through 2015. These avoided costs are similar to other avoided costs commonly included in value of solar studies. Highlights: We estimate how distributed PV reduced short-term electricity prices from 2013 to 2015. We simulate hourly generation by each distributed PV system in California. Distributed PV reduced hourly mean wholesale electricity prices by 8–9%. Lower prices reduced utilities' costs by up to $650–730 million from 2013 to 2015.